H3K9 Acetylation of Tph2 Involved in Depression-like Behavior in Male, but not Female, Juvenile Offspring Rat Induced by Prenatal Stress. (15th June 2018) - Dang, Shaokang; Lu, Yong; Su, Qian; Lin, Tianwei; Zhang, Xiaoxiao; Zhang, Huiping; Zhang, Junli; Zhang, Lin; Zhu, Zhongliang; Li, Hui
Highlights: Prenatal stress (PS) causes depression-like behavior in male juvenile offspring rats (MJORs). TSA (a broad-spectrum inhibitor for HDAC I and HDAC II) reverses the effect of PS on depression-like behavior. PS affects TPH2 expression in the dorsal raphenucleus and hippocampus of MJOR. TSA reverses the effect of PS on TPH2 expression. TSA reverses PS-induced Tph 2 H3K9ac level decline in hippocampus in MJOR. Abstract: Increasing evidence has shown that prenatal stress (PS) could cause depression-like behavior in the offspring, which is sex-specific. However, the underlying mechanisms remain to be elucidated. This study is to investigate the involvement of tryptophan hydroxylase 2 ( Tph 2) H3K9 acetylation (H3K9ac) modification on PS-induced depression-like behavior in juvenile offspring rats (JOR). PS models were established, with or without trichostatin A (TSA) treatment. Animal behavior was assessed by the sucrose preference test (SPT) and forced swimming test (FST). The mRNA and protein expression levels of TPH2 in the dorsal raphenucleus (DRN), hippocampus, and prefrontal cortex were detected with quantitative real-time PCR and Western blot analysis, respectively. The Tph 2 H3K9ac levels in the hippocampus were also analyzed. SPT and FST showed significantly reduced sucrose preference and significantly prolonged immobility in PS-induced male juvenile offspring rats (MJOR). Moreover, the mRNA and protein expression levels of TPH2 in the DRN and hippocampus were significantly declined, while the hippocampal Tph 2 H3K9ac levels were significantly declined in the PS-induced MJOR. Furthermore, the PS-induced effects in MJOR could be reversed by the microinjection of TSA. However, no significant effects were observed for the female juvenile offspring rats (FJORs). In conclusion, our results showed that the Tph2 H3K9ac modification is only involved in PS-induced depression-like behavior in MJOR, in a sex-specific manner. These findings might contribute to the understanding of the disease pathogenesis and clinical treatment in future.